STRATEGY OF DIFFERENTIATED MULTI-STAGE THERAPY OF PROXIMAL SPINAL AMIOTROPHY IN CHILDREN - M.R. SHAYMURZIN (Avicenna Tajik State Medical University, 2019)
Objective: To assess the results of the treatment of spinal muscular atrophy (SMA) in children using international scales of physical capacity assessment and computer electroneuromyography on different stages of the disease. Methods: 95 children with a genetically confirmed diagnosis of proximal SMA from Donetsk region and other regions of Ukraine, as well as neighboring countries were under observation. All patients, depending on the therapy, were divided into two groups: the main group consisted of 65 children (68.4%), who received treatment based on the method developed by us; the control group comprised 30 children (31.6%) who received general therapy incorporating drugs from the metabolite group in age dosages and symptomatic drugs. Results: An interim evaluation of the effectiveness of therapy was carried out after 2 years, the final assessment - based on 4 years of catamnesis observation by statistical processing of patient's physical performance assessments. According to the interim and final results, the severity of the clinical condition is reliably higher in patients of the control group with the SMA II and III type. Conclusion: A comprehensive approach to the evaluation of the treatment of SMA, both from a clinical and additional research perspective, effectively promotes differentiated phases selecting therapies aimed at slowing down the pathological process, preventing complications and improving the quality of life.